Combining the microbial agent Rhodopseudomonas palustris strain PSB-06 with fungicides for controlling rice blast - Wu, Xiyang; Chen, Yue; Chen, Chunyan; Huang, Qiang; Qin, Yingfei; Zhang, Xin; Li, Chenggang; Tan, Xinqiu; Liu, Yong; Zhang, Deyong (Frontiers in Sustainable Food Systems, 2022)
The rice blast disease caused by Magnaporthe oryzae threatens global rice production yields. Tricyclazole and isoprothiolane are widely used fungicides with high activity against rice blast, and our previous study indicated the photosynthetic bacterium Rhodopseudomonas palustris PSB-06 significantly antagonizes rice blast. However the effect of combining these two chemical fungicides with PSB-06 on rice blast control is unclear. Here we test the control effect of photosynthetic bacteria PSB-06 combined with isoprothiolane and tricyclazole on rice blast. The growth of PSB-06 was unaffected by up to 1.25 mg/L of tricyclazole and 0.3 mg/L of isoprothiolane in the photosynthetic medium, indicated the two fungicides have no inhibition on PSB-06. The control efficiency in the field test reached 76.06% when PSB-06 was combined with isoprothiolane. This value was significantly higher than the individual efficiency of PSB-06 (67.99%) and tricyclazole (65.46%) and the combined control efficiency (72.20%) of those two antifungal agents. Our current findings highlighted the potential of combining R. palustris strain PSB-06 with isoprothiolane to control rice blast, providing environmental protection and reducing the use of fungicides.